1995
DOI: 10.1016/0042-6989(94)00254-j
|View full text |Cite
|
Sign up to set email alerts
|

Underwater refraction-polarization patterns of skylight perceived by aquatic animals through Snell's window of the flat water surface

Abstract: The grass shrimp (Palaemonetes vulgaris) orients itself by means of the polarization pattern of the sky visible through Snell's window of the water surface. The celestial polarization pattern viewed from water is distorted and modified because of refraction and repolarization of skylight at the air-water interface. This work provides a quantitative account of the repolarization of skylight transmitted through a flat water surface. The degree and direction of linear polarization, the transmissivity and the shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 31 publications
0
56
0
1
Order By: Relevance
“…This polarization feature arises from the following: The reflection-polarization characteristics of the water surface are determined by two light components: (1) light reflected from the water surface, and (2) light originating from below the water surface. Component 1 is usually horizontally polarized because of reflection polarization of sunlight/moonlight and skylight from the air-water interface [8], while component 2 is always vertically polarized due to the refraction polarization of subsurface light at the water-air interface [10]. If component 1 or 2 dominates, the net polarization of water-returned light is horizontally or vertically polarized, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This polarization feature arises from the following: The reflection-polarization characteristics of the water surface are determined by two light components: (1) light reflected from the water surface, and (2) light originating from below the water surface. Component 1 is usually horizontally polarized because of reflection polarization of sunlight/moonlight and skylight from the air-water interface [8], while component 2 is always vertically polarized due to the refraction polarization of subsurface light at the water-air interface [10]. If component 1 or 2 dominates, the net polarization of water-returned light is horizontally or vertically polarized, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Coulson indicated that the single Rayleigh scattering model can effectively describe the polarized skylight in theory [43]. However, considering the atmospheric disturbances such as multiple scattering, ground reflection, aerosol and the anisotropic of molecules, we compute the skylight polarization patterns using the semi-empirical Rayleigh scattering model [7,43], which is expressed as below.…”
Section: Intensity and Polarization Of Skylightmentioning
confidence: 99%
“…Then, we can describe the variation of the polarization when light passes through the air-water interface using the Mueller matrix, and the Mueller matrix of refraction at an interface can be derived using Fresnel's formulas and is shown in Equation (6) [7].…”
Section: Polarization Characteristics Of Refracted Lightmentioning
confidence: 99%
See 2 more Smart Citations